Diurnal changes of mineral and organic compounds in the rhizosphere soil of plants growing in sites with different soil parameters - Shtangeeva, Irina; Chelibanov, Vladimir; Golovin, Alexander; Ryumin, Alexander (International Journal of Sustainable Energy and Environmental Research, 2025)
There is a growing demand for efficient identification of different compounds in the rhizosphere soil. The main aims of this work were to conduct field experiments to identify possible differences in the composition of bulk soils in different sites, as well as in the rhizosphere soil, arising as a result of plant growth in sites with different soil characteristics and to study short-term (during daylight hours) variability in the composition of the rhizosphere soil. Soil samples were collected several times during the day at three sites characterized by different soil parameters. The soil taken from the roots of a widespread weed, nettle, and bulk soil (taken from the top layer of soil in the sites) were analyzed by Raman spectroscopy. The soil spectra showed bands of various organic and mineral compounds. The pH of bulk soils collected in the sites varied and depended on the type of soils and their composition, primarily on the amount of carbon and some minerals in the soils. This was observed even when the differences between the soil parameters in the sites were small. The content of different compounds in the rhizosphere soil was not constant but changed during the day. These changes were regular and varied across the three sites. It was assumed that the main factors influencing these variations were circadian fluctuations of root exudates and soil characteristics. Given the short-term variability of different compounds in the rhizosphere soil, sampling time should be chosen carefully to ensure correct interpretation of experimental data.